Essentials : - Fox, Marianne (Pearson, 2004)
Backed with over 20 years of writing, teaching and professional experience with electronic spreadsheets, the authors have perfected the format and presentation of material for every type learning style. Comprehensive information for students at many levels of experience and a flexible binding make this a must-have series for applications essentials. Areas covered include taking a tour of Excel, creating a worksheet, improving worksheet appearance, producing/printing well-designed worksheet, working with functions, sorting and filtering lists, working with charts, developing a multiple-sheet workbook, creating special effects in a worksheet, changing data in a workbook, formatting and displaying worksheets, documenting/protecting worksheets, integrating applications, using functions to create/analyze data, creating pivot tables and pivot charts and hyperlinks and collaborative tools, designing online forms with Excel, automating tasks with macros, using database functions, expanding charting skills, auditing and customizing worksheets, guiding cell entry—data validation, using problem-solving tools and managing data from multiple sources. For training professionals.